(untitled) (Research, Society and Development, 2021)
An important sector of world agriculture, potato cultivation stands out because its production presents difficulties and challenges, among them is the adequate management of fertilization, mainly of nitrogen. With this work, the objective was to test sources and doses of nitrogen in the emergence of potatoes cv Ágata, The work was carried out in the field at the experimental unit of the Federal University of Fronteira Sul, Laranjeiras do Sul campus, in the Horticulture sector. Three sources of fertilization were used, tanned poultry litter, pelleted poultry litter and humus with five different doses, 120, 140, 160, 180, 200 kg-¹, and two NPK 160 and 200 kg-¹, testemun controls. . Seed potatoes were supplied by UNICENTRO, planting took place in October. The variables evaluated 14 days after sowing were the number of emerged tubers and the incidence of rot in the tubers. The presence of 100% of the tubers of Pectobacterium sp. The highest percentage of emergence was obtained with the control, NPK 200 kg-¹, followed by pelletized poultry litter 120 kg-¹. The use of tanned poultry litter 140 kg-¹ provided a smaller number of emerged potatoes. It is concluded that the NPK 200 kgha-¹ showed higher values than the other treatments, however it is not usually used by potato growers. The pelleted poultry litter at a dose of 120 kg-¹ has the best cost-benefit ratio and emergence percentage among organic fertilizers.